Separation of Vowel Sequences by Consonant Addition in a Child’s Bilingual Development - Babatsouli, Elena (Journal of Monolingual and Bilingual Speech, 2020)
Studying infrequent variants in child developmental speech is insightful for language representation and processing. Phonological processes like anticipation and perseveration account for such productions in children. How children process such infrequent variants during development has not been fully explored. In particular, there is no study on the separation of within-word vowel sequences by consonant addition in monolingual or bilingual children. The present study investigates this in a bilingual child’s phonological development in English and Greek, from age 2;7 to 3;9. Sufficient data were obtained for English diphthongs and hiatus and Greek hiatus. Results show that Greek, the stronger language by 1 MLU, interferes with perseverations in English between code-switched utterances. Such consonant additions, which are more frequent in the stronger language, decrease with age in both languages. While anticipation overall increases with age in both languages, within-word perseveration also increases. Word-position frequency of vowel sequences and of their added consonants in the words triggering them, as well as processing distance, are language and process (anticipation/perseveration) dependent. The results offer insights into error processing in child monolingual and bilingual speech.